The Characterization of Topeng Panji Cirebon Through Judgment Evaluation At Topeng Gegesik Book in Indonesian Version (Appraisal Theory) - Iswandi, Fedro; Firdaus, Arief; Widyasari, Widyasari (UIR Press, 2025)
This study investigates about the characterization of topeng Panji Cirebon at Topeng Gegesik book. The focus of research is to analyze the types of judgment evaluation that represents in the source language text (Indonesian version). The data are words and clauses which it indicates judgment and the data source is Topeng Gegesik book. Next, the research design is descriptive qualitative and the data were obtained through documentation (document analysis). Then, data is analyzed by using data collection, display, conclusion drawing-verifying. The last, research findings showed that there are two types of judgment namely social esteem and social sanction. Social esteem includes normality and social sanction is propriety and tenacity. Furthermore, positive normality is used more dominant by the author with 7 data frequency. Next, it is followed by positive propriety with 5 data frequency. Based on the research findings, the author predominantly employs positive normality and positive propriety that the author portrays topeng Panji Cirebon in a positive and respectful manner with social norms and moral values. The use of positive judgment suggests an attention to both appreciate and legitimize the cultural and ethical significance of topeng Panji Cirebon.